TGF-β1, but not bone morphogenetic proteins, activates Smad1/5 pathway in primary human macrophages and induces expression of proatherogenic genes - Nurgazieva, Dinara; Bieback, Karen; Goerdt, Sergij; Kzhyshkowska, Julia (The journal of immunology, 2015)
Macrophages are responsible for the control of inflammation and healing, and their malfunction results in cardiometabolic disorders. TGF-β is a pleiotropic growth factor with dual (protective and detrimental) roles in atherogenesis. We have previously shown that in human macrophages, TGF-β1 activates Smad2/3 signaling and induces a complex gene expression program. However, activated genes were not limited to known Smad2/3-dependent ones, which prompted us to study TGF-β1-induced signaling in macrophages in detail. Analysis of Id3 regulatory sequences revealed a novel enhancer, located between +4517 and 4662 bp, but the luciferase reporter assay demonstrated that this enhancer is not Smad2/3 dependent. Because Id3 expression is regulated by Smad1/5 in endothelial cells, we analyzed activation of Smad1/5 in macrophages. We demonstrate here for the first time, to our knowledge, that TGF-β1, but not BMPs, activates Smad1/5 in macrophages. We show that an ALK5/ALK1 heterodimer is responsible for the induction of Smad1/5 signaling by TGF-β1 in mature human macrophages. Activation of Smad1/5 by TGF-β1 induces not only Id3, but also HAMP and PLAUR, which contribute to atherosclerotic plaque vulnerability. We suggest that the balance between Smad1/5- and Smad2/3-dependent signaling defines the outcome of the effect of TGF-β on atherosclerosis where Smad1/5 is responsible for proatherogenic effects, whereas Smad2/3 regulate atheroprotective effects of TGF-β.